The complete mitochondrial genome of the swimming crab Charybdis natator (Herbst) (Decapoda: Brachyura: Portunidae) and its phylogeny. Issue 2 (2nd January 2017) - Yang, Xiaolong; Ma, Hongyu; Waiho, Khor; Fazhan, Hanafiah; Wang, Shuqi; Wu, Qingyang; Shi, Xi; You, Cuihong; Lu, Jianxue
Abstract: The complete mitochondrial genome of Charybdis natator (family Portunidae) was obtained using Illumina and Sanger dideoxy sequencing. This genome was a typically circular molecule with a length of 15, 664 bp and encoded 13 protein-coding genes, 22 transfer RNA genes and 2 ribosomal RNA genes. The overall base composition of this mitogenome was 34.00% for A, 11.06% for G, 36.36% for T, and 18.58% for C, respectively, with a higher A + T content (70.36%). The gene composition and arrangement were accordant to the closely published species. The phylogenetic analysis suggested that C. natator had the closest relationship with C. japonica .